Customer Satisfaction as an Intervening Variable in the Effect of Social Media Marketing and Brand Trust on Repurchase Intention - Ranni Iqlima Putri; Yuli Kartika Dewi (Jurnal Manajemen Bisnis, 2026)
The rapid development of digital technology has transformed marketing practices and consumer behavior, particularly through the use of social media. This study aims to analyze the effects of social media marketing and brand trust on repurchase intention, with customer satisfaction serving as an intervening variable, in the context of cold chain logistics at HSN Group. The study employs a quantitative approach with an explanatory research design, using primary data collected from 100 customers who have used HSN Group’s services and interacted with the company’s social media platforms. Data were collected through an online questionnaire and analyzed using Partial Least Squares–based Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS 4 software. The results indicate that social media marketing has a positive and significant effect on customer satisfaction and repurchase intention. Brand trust is shown to have a positive and significant effect on customer satisfaction, but it does not have a direct effect on repurchase intention. These findings underscore the important role of customer satisfaction in strengthening long-term relationships with customers and encouraging repeat purchases.